Politics and Psychology of Fear: Threat Narratives in State Security Policy - Samsidar Samsidar (Pt. Anagata Sembagi Education, 2025)
This study examines how the politics of fear is shaped and exploited through threat narratives in state security policy. Using a qualitative approach and literature study methods, this study analyzes the dynamics of discourse used by the state to legitimize repressive security measures. Threat narratives, discursively constructed by state actors and amplified by the media, play a central role in shaping public perceptions of imminent danger. The resulting collective fear allows the state to justify enacting extraordinary policies, even when there is no real, proportionate threat. Within the framework of securitization and state of exception theories, security policy is interpreted as a response to politically defined, rather than objective, threats. As a result, the space for public participation is narrowed, civil rights are diminished, and the rule of law is threatened. This study emphasizes that security cannot be built on manipulative constructs of fear but must be grounded in transparency, justice, and respect for democratic principles. Critique of the politics of fear is crucial to ensure that security policy does not deviate from the framework of a democratic and civilized state based on the rule of law.